Metagenomics: an emerging tool for the chemistry of environmental remediation - Offiong, Nnanake-Abasi O.; Edet, John B.; Shaibu, Solomon E.; Akan, Nyaknno E.; Atakpa, Edidiong O.; Sanganyado, Edmond; Okop, Imeh J.; Benson, Nsikak U.; Okoh, Anthony (Frontiers in Environmental Chemistry, 2023)
Metagenomics is the study of genetic information, including the sequences and genomes of microorganisms present in an environment. Since 1998, the full-scale application of this technique to environmental chemistry has brought significant advances in the characterization of the nature and chemical composition/distribution of contaminants present in environmental matrices of contaminated and/or remediated sites. This has been critical in the selection of microorganisms and has contributed significantly to the success of this biological treatment over the years. Metagenomics has gone through different phases of development, which ranges from initial sequencing strategies to next generation sequencing (NGS), which is a recently developed technology to obtain more robust deoxyribonucleic acid (DNA) profile of microorganisms devoid of chimeric sequences which reduces the quality of metagenomic data. Therefore, the objective of this review is to evaluate the applications of metagenomics in the understanding of environmental dynamics of chemical contaminants during remediation studies. . Also, this review presents the relationship between biological characteristics of microorganisms and chemical properties of chemical compounds, which forms the basis of bioremediation and could be useful in developing predictive models that could enhance remediation efficiency. In conclusion, metagenomics techniques have improved the characterisation of chemical contaminants in the environment and provides a correlation for useful prediction of the type of contaminant expected in various environmental matrices.